Empowering wound care nurses in the assessment and early detection of diabetic foot ulcers through Indonesia-Malaysia international collaboration - Haryanto, Haryanto; Khairillah, Yuyun Nisaul; Fitriana, Erlis Eka; Mentari, Tiara Amalia (Community Empowerment, 2025)
This community service initiative aimed to enhance the knowledge and skills of wound care nurses in the assessment and early detection of diabetic foot ulcers (DFU). The program was a collaborative effort between the Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat and Universiti Malaysia Sarawak (UNIMAS). The methodology included lectures, discussions, hands-on practice, and evaluation using a one-group pre-test and post-test design to measure the intervention's effectiveness. Results demonstrated a significant increase in nurses' knowledge, with the average pre-test score improving from 75 to 88 after the intervention. This indicates that international collaboration is effective in improving the knowledge and skills of wound care nurses. Furthermore, regular, scheduled training sessions are recommended to maintain and enhance nurses' competency in diabetic wound management.